The Influence of Project Based Learning on Students Critical Thinking Ability at Muhammadiyah 1 Bangunrejo Senior High School - Anjarwati, Sulis; Purnamasari, Alvina Putri; Novitasari, Cici (Universitas Sembilanbelas November Kolaka, 2024)
This study is based on the existence of learning activities that are still affected by the Covid-19 virus where learning only relies on material delivered by teachers through learning groups without any interaction that trains collaboration and critical thinking skills of students. This study aims to determine the effect of using the project-based learning model (PjBL) on students' critical thinking skills. The research design uses a pretest-posttest control group design, the research procedure is carried out through preparation, implementation of research, and conclusion. The instruments used are essay questions and instrument sheets with indicators of critical thinking skills. The data analysis technique for the pretest-posttest results uses the t-test (independent sample t-test). The highest critical thinking ability is found in the conclusion-drawing indicator with a value of 86.80. The hypothesis test obtained a t count value of 2.48 and a t table of 1.99, which means that the use of the PjBL learning model has a significant influence on students' critical thinking skills. Based on the results of the hypothesis test, it is known that the project-based learning model (PjBL) has an effect on the critical thinking skills of students at SMA Muhammadiyah 1 Bangurejo.